Abnormalities in the cerebellar levels of trophic factors BDNF and GDNF in pcd and lurcher cerebellar mutant mice - Salomova, Martina; Tichanek, Filip; Jelinkova, Dana; Cendelin, Jan (Neuroscience letters, 2020)
Hereditary cerebellar degenerations are severe and complex diseases for which there is currently no effective causal treatment. A hopeful method could be the support of plasticity or neurotransplantation. However, there are still many unknown aspects which could influence the outcome of treatment. As neurotrophic factors are essential in neuroplasticity and neuronal integration, potential abnormalities in their levels could be involved in the pathogenesis of the disease and would possibly explain the unsuitability of diseased cerebellum for the graft integration. The aim of this study was to identify and compare basal levels of trophic factors BDNF and GDNF in the cerebellum in two mouse models of cerebellar degeneration - Lurcher and pcd. Basal levels of BDNF in the cerebellum have been shown to be lower in both mutant models than in healthy controls. However, the GDNF levels were surprisingly increased in the cerebella of Lurcher mutant mice compared to both wild type and pcd mice. In addition, a different distribution of GFAP-positive cells in the cerebellum was revealed in Lurcher mice. These differences suggest that the niche of the Lurcher mutant cerebellum is changed. The question, however, remains how these changes are related to the neurodegenerative process and how they could influence potential compensatory mechanisms, plasticity and response to therapeutic interventions.
Keywords: mutace; Animals; myši transgenní; Neurodegenerative Diseases; Mice, Neurologic Mutants; BDNF; biologické markery; Lurcher mouse; Pcd mouse; Biomarkers; Mice, Transgenic; mozeček; Mice; Cerebellar degeneration; Mutation; neurodegenerativní nemoci; myši; růstový faktor GDNF; GDNF; Glial Cell Line-Derived Neurotrophic Factor; Mice, Inbred CBA; Brain-Derived Neurotrophic Factor; Cerebellum; mozkový neurotrofický faktor; zvířata; myši inbrední CBA; myši - mutanty neurologické